Adapting the two-node model to evaluate sleeping thermal environments - Yan, Shujie; Xiong, Jing; Kim, Jungsoo; de Dear, Richard (Building and environment, 2022)
While it is evident that thermal environment plays a significant role in human sleep quality, currently there remains a paucity of literature on the assessment of sleeping thermal environment. In this study, the two-node model has been adapted to evaluate sleeping thermal environments through two phases of work - modifications to the model's inputs and coefficients, and the conversion to a transient model. A calculation method for the model's key input intrinsic bedding insulation, Icl,bed, was proposed. The default heat transfer coefficients in the two-node model were replaced with the values corresponding to a supine human body. The two-node model's algorithm was adapted from its default, steady-state solution to a transient, time-series approach, to accommodate transients in both thermal environmental and physiological parameters through the course of the night. The modified two-node model was used to identify the optimum summer SET*sleep in a Sydney sleep survey database. Nocturnal mean skin temperatures predicted by the modified two-node model agree with the published physiological data in the literature. The upper limit of the Sydney summer bedroom SET*sleep for sleeping persons was 31 °C. In addition, the upper limit of summer operative temperatures was also determined for typical bedding systems. For instance, for the combination of short-sleeved sleepwear and Quilt1 (Warmth level 1), the upper limit of bedroom temperature was recommended to be 26.5 °C. Finally, the bedroom temperature control strategy for optimal sleep thermal comfort was predicted. •Two-node model was adapted to evaluate sleeping thermal environments.•An estimation method for the intrinsic bedding insulation (Icl,bed) was proposed.•The upper limit of summer SET*sleep was identified based on a sleep quality survey database.•Upper limits of summer bedroom operative temperatures for nine common bedding systems were obtained.